The features of the socio-psychological climate in collectives of healthcare institutions. - Vezhnovets, T. A. (Medicni Perspektivi, 2016)
The purpose of the research was to determine the features of the socio-psychological climate of health care institutions (HCI) and the factors that cause them. The psychological testing of the socio-psychological climate has been accomplished by the method of A. Nemov “The socio-psychological self-esteem of a collective”, The study involved 152 health care workers of two hospitals in Kherson region (institution N 1 and institution N 2), providing multidisciplinary patient care. It was found that the group of health care workers in the institution N 1 had significantly lower average age and average length of joint work than personnel of the institution N 2 (P<0.007). It was determined that all indicators of climate (responsibility, openness, teamwork, contact, cohesion, orderliness and awareness) had significantly lower levels of the values in the institution N 1, than in the institution N 2 (P<0.007). The worst state of the socio-psychological climate was indicated by the personnel of the institution N 1. In two institutions indicator of team cohesion had the lowest value among all. The direct correlation between the average age and the length of experience of joint work in the collective and the value of indicators of the socio-psychological climate in the team has been established. The status of the socio-psychological climate in HCI collectives is affected by the age of health care workers and the experience of joint work. It was found, that the lower average age and experience of joint work of health care workers, the lower indicators of the socio-psychological climate in the collective are. The feature of the socio-psychological climate of HCI collectives is low evaluation of indicator of cohesion by health care personnel. This testifies to the expressed individuality in actions. The peculiarities of the socio-psychological climate in collectives of health care workers should be considered when evaluating the effectiveness of personnel management in HCI.